Differences in Students' Knowledge and Attitudes when Given Media, Games, Esedalu, and Videos on Healthy Clean Living Behavior in State Elementary School 146 Gumuruh, Bandung City - Lolan, Yosef Pandai; Firdaus, Rendy; Kurniawati, Ratna Dian; Suherdin, Suherdin (Universitas Ibn Khaldun Bogor, 2024)
Clean and Healthy Living Behavior (PHBS) is an effort to transmit experiences about healthy living behavior through individuals, groups or communities. Infectious diseases are often experienced by elementary school (SD) children who are susceptible to various diseases caused by habits and the environment, one of which is diarrhea, the prevalence of diarrhea in West Java province shows an increase from 4.5% in 2013 to 6.8% in 2018 and based on the characteristics of the age group 5-14 years diarrhea cases as many as 182,338 people or equivalent to 6.05% of cases in 2018. In the percentage of Bandung Regency or City the percentage of clean and healthy living behavior has not reached half in 2007 of 16.6%, in 2013 of 23.2%, and in 2018 of 49.6%. The type of research used in this study is a Quasi-Experimental design, the approach used is a non-equivalent control group (pretest-posttest). The number of samples in this study was 15 respondents of the first treatment, 15 respondents of the second treatment, and 15 respondents of the control group with a total sample of 45 respondents in this study. The average score of knowledge in the results of the study increased after the intervention of health education with video media, aksedalu and control groups where before the intervention was given the average value of each group with video media was 13.00, Aksedalu 11.00, and in the control group of 12.47, the value of attitude before intervention using media was obtained value 6.18, and the value of attitude after intervention using media was obtained value 7.42. It is said that respondents received information provided through health education with videos and aksedalu given in 3 interventions until the increase in knowledge.